PERAN PERWAKILAN OMBUDSMAN REPUBLIK INDONESIA PROVINSI BALI DALAM PENGAWASAN PENYELENGGARAAN PELAYANAN PUBLIK (Studi Kasus : Pelayanan Publik Bidang Pendidikan di Kota Denpasar) - Prabawati, Ni Putu Anik; Dewi Pascarani, Ni Nyoman; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2015)
ABSTRACT Education Services in Denpasar have been frequently covered by the media particularly several  issues  regarding  fraud  in  the  implementation  of  the  National  Examination  and  the Admission of new students. In addition, the Bali Provincial Representative of  the Republic of Indonesia Ombudsman also received many complaints related to the implementation of public services in  education in  the City of  Denpasar. Based on these problems, this study aims to determine how the role of the Bali Provincial Representative of the Republic of Indonesia Ombudsman in implementing the monitoring of public services related to education in the City of Denpasar. The findings show that the supervision or monitoring conducted by the Bali Provincial Representative of the Republic of Indonesia Ombudsman has given good results.   Keywords: Roles, Monitoring, Public Service, Education.